The Implementation of Interactive Reading Approach in English Language Learning at SMP Negeri 30 Bengkulu Tengah - Oktafiani, Aisyah; Hakim , Arif Rahman; Putra, Pebri Prandika (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This research explored the application of the Interactive Reading Approach (IRA) in the teaching of narrative texts to eighth-grade students at SMP Negeri 30 Bengkulu Tengah. The study was carried out in response to students’ low reading comprehension and the lack of active interaction during English lessons. It aimed to portray how IRA was implemented in the classroom, analyze patterns of interaction between teachers and students, and identify challenges encountered throughout the learning process. Using a qualitative descriptive design, the data were collected through classroom observations, semi-structured interviews with both teachers and students, and relevant documents, and were analyzed through coding, thematic analysis, and triangulation. The results indicated that IRA was conducted through a series of pre-reading, while-reading, and post-reading activities, which promoted students’ active involvement in interpreting narrative texts through discussion and guided support from the teacher. Although challenges such as limited vocabulary mastery, uneven student participation, and limited learning resources were encountered, the findings suggest that the Interactive Reading Approach contributed positively to classroom interaction and supported students’ reading comprehension.